Prevalence and Spectrum of SDHx Mutations in Pheochromocytoma and Paraganglioma in Patients from Belgium: An Update - Persu, A.; Lannoy, N.; Maiter, D.; Mendola, A.; Montigny, P.; Oriot, P.; Vinck, W.; Garin, P.; Hamoir, M.; Vikkula, M. (Hormone and Metabolic Research, 2012)
Since the early 2000s, the prevalence and spectrum of mutations in genes encoding subunits of succinate dehydrogenase (SDHx) were reported in large cohorts of patients with pheochromocytoma (PC) and paraganglioma (PGL) from most Western countries. Unfortunately, in Belgium, no equivalent work was performed thus far. Therefore, the aim of the work was to look for mutations in SDHx genes and genotype-phenotype correlations in patients with PC and/or PGL from Belgium. Screening of the coding parts of SDHx genes and deletion search were performed in all patients with PC and/or PGL referred to the Cliniques Universitaires Saint-Luc from 05/2003 to 05/2011. Genetic screening was performed in 59 unrelated head and neck (hn)PGLs (8 familial) and 53 PCs (7 extra-adrenal; 3 metastatic). In hnPGLs, 10 different SDHD mutations (3 substitutions, 5 deletions, 2 splice site mutations) were detected in 16 patients, including 7 familial cases and 9 apparently sporadic cases. In the same subset, we found 8 different SDHB mutations (5 substitutions, 1 splice site mutation, 1 deletion, 1 duplication) in 10 patients with sporadic hnPGL without evidence of malignancy. No SDHx mutation was detected in patients harboring PCs and no SDHC mutation whatsoever. In conclusion, in our multicentric database of PC-PGLs from Belgium, (i) the prevalence of SDHx mutations was high in hnPGLs (44% in the whole subset, 37% of apparently sporadic cases); (ii) in sporadic cases, the prevalence of SDHB mutations was high (20%), similar to that of SDHD (18%); and (iii) no SDHx mutation was found in a subset of mostly adrenal, benign PCs.
Keywords: SDHD; SDHB; SDHC; VHL; glomic tumors; adrenal tumors